Latent profile analysis of fatalism and its influencing factors among community-dwelling disabled elderly individuals - Jinlei Du; Xiaoling Wu; Qiyu Zhang; Yuanxia Wang; Yao Chen; Chencong Nie (Frontiers in Psychology)
ObjectiveThis study aims to explore the latent profiles of fatalism among community-dwelling disabled elderly individuals and identify the key factors influencing these profiles. The findings will provide valuable insights for formulating tailored care management strategies for this population.DesignA cross-sectional survey study.MethodsA random sampling approach was used to survey disabled elderly individuals residing in 109 communities across eight urban districts in Sichuan Province. Data were collected through a general information questionnaire and a Fatalism Scale. Latent profile analysis was performed to identify distinct fatalism profiles, and multivariate unordered regression analysis was conducted to assess their influencing factors.ResultsThree distinct latent profiles of fatalism were identified: high fatalism and pessimism tendency (35.6%), moderate fatalism and low optimism tendency (9.6%), and low fatalism with relative optimism tendency (54.8%). Multivariate analysis revealed that living arrangements, number of children, educational level, duration of disability, and self-reported economic stress were significant factors influencing these fatalism profiles.ConclusionThere is significant heterogeneity in fatalism among community-dwelling disabled elderly individuals. Caregivers and healthcare managers can develop more precise and personalized management strategies by considering the different latent profiles and their associated influencing factors.